2008
DOI: 10.1002/eco.4
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for understanding semi‐arid land degradation: ecohydrological interactions across multiple‐space and time scales

Abstract: 15Land degradation is a problem prolific across semi-arid areas world-wide. Despite 16 being a complex process including both biotic and abiotic elements, previous attempts 17 to understand ecosystem dynamics have largely been carried out within the disparate 18 disciplines of ecology and hydrology which has led to significant limitations. Here, an 19 ecohydrological framework is outlined, to provide a new direction for the study of 20 land degradation in semi-arid ecosystems. Unlike other frameworks that draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
241
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(259 citation statements)
references
References 103 publications
3
241
0
4
Order By: Relevance
“…Sediment connectivity is based on the interplay of structural components (morphology) and process components (flow of energy/transport vectors and materials) that determine the longterm behaviour of the sediment flux which is manifest as a change in landform (Preston and Schmidt, 2003;Turnbull et al, 2008;Bracken et al, 2013). Thus, sediment connectivity is dependent not on individual processes, but on all aspects of the geomorphic system that control sediment flux -processes of detachment, entrainment and transport -but also the emergent characteristics of sediment deposition and sediment residence times (Preston and Schmidt, 2003;Sandercock and Hooke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment connectivity is based on the interplay of structural components (morphology) and process components (flow of energy/transport vectors and materials) that determine the longterm behaviour of the sediment flux which is manifest as a change in landform (Preston and Schmidt, 2003;Turnbull et al, 2008;Bracken et al, 2013). Thus, sediment connectivity is dependent not on individual processes, but on all aspects of the geomorphic system that control sediment flux -processes of detachment, entrainment and transport -but also the emergent characteristics of sediment deposition and sediment residence times (Preston and Schmidt, 2003;Sandercock and Hooke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is thus ambiguous under different environmental conditions (Bautista et al, 2007). For example, a positive correlation between plant diversity and soil erosion has frequently been observed; however, a negative correlation has also been found (Turnbull et al, 2008). After conducting research in the Netherlands, Martin et al (2010) found that different vegetation conditions give rise to different correlations between plant diversity and soil erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with changes in hydrological function, changes in ecosystem structure may precipitate a potentially catastrophic shift to a much less stable ecosystem state [Turnbull et al, 2008a] with an increased vulnerability to fluvial erosion. Data from two woody landscapes in basin and montane ecotones, which may be analogous with large areas of the basin and range southwestern U.S., showed that not only more organic C was eroded per unit area than in pristine grasslands Journal of Geophysical Research: Biogeosciences 10.1002/2014JG002635 but that this included large quantities of previously stabilized organic C from legacy grasslands.…”
Section: Resultsmentioning
confidence: 99%
“…However, woody encroachment in drylands alters ecosystem structure and function [Barger et al, 2011;Turnbull et al, 2008a], potentially leading to degradation [Okin et al, 2009;D'Odorico et al, 2013]. The change in structure, following encroachment, is often characterized by a reduction in vegetation cover [Turnbull et al, 2010a] and increased heterogeneity in both soil and vegetation resources [Dickie and Parsons, 2012;Bhark and Small, 2003].…”
Section: Introductionmentioning
confidence: 99%